Lexicographic Analysis of Al-Mu'jam Al-'Arabiy Baina Yadaik: A Study on Its Type and Features - Ismi Latifah Fauziah; Syihabuddin Syihabuddin (Universitas Muhammadiyah Gorontalo, 2025)
Dictionaries are essential tools that facilitate understanding of word meanings and enhance vocabulary mastery, especially for non-native speakers. They not only serve as translation aids but also help learners understand word origins, forms, synonyms, and antonyms, which are crucial for effective communication in a globalized world. Dictionaries are the end product of lexicography. The aim of this research is to identify and categorize the types of dictionaries found in Al-Mu'jam Al-'Arabiy Baina Yadaik including the characteristics and functions of each type. Furthermore, the research aims to explore the features that support language learning within this dictionary, such as the organization of entries, the use of illustrations, and the presentation of information that facilitates comprehension for Arabic language learners. This research is a qualitative study with descriptive analysis employing a literature review approach. The results of this article categorize this Dictionary as a monolingual, specialized, printed, pocket, and visual dictionary. Key features supporting language learning include phonetic alphabetical order, consistent verb conjugation formats, contextual usage examples, and references to verses from the Quran.